Identification of a lncRNA based signature for pancreatic cancer survival to predict immune landscape and potential therapeutic drugs - Ma, Di; Yang, Yuchen; Cai, Qiang; Ye, Feng; Deng, Xiaxing; Shen, Baiyong (Frontiers in Genetics, 2022)
Pancreatic cancer is one major digestive malignancy with a poor prognosis. As the clinical value of lncRNA was emphasized, developing novel molecular markers with lncRNAs for pancreatic cancer has great potential. Therefore, the expression profile and prognostic value of lncRNAs in the PAAD cohort from TCGA were examined, and an 8-lncRNA-based robust prognostic signature was constructed using a random survival forest model. The efficacy and effectiveness of the lncRNA-based signature were thoroughly assessed. Patients with high- and low-risk defined by the signature underwent significantly distinct OS expectancy. Most importantly the AUCs of ROC in the training group reached 0.90 and the testing group was also above 0.86. After combined analysis with other clinical-pathological factors in Cox regression and nomogram, the lncRNA-based signature was proven to function as a prognostic indicator of pancreatic cancer, either alone or simultaneously with other factors. In addition, the immune landscape and differences in biological processes between high- and low-risk subgroups were investigated via GSEA and CIBERSORT scoring methods. Last but not least, potential therapeutic molecules targeting high-risk patients were explored in drug databases. As the result, Afatinib, LY-303511, RO-90-7501 were the most promising agents. To sum up, we developed a novel lncRNA based prognostic signature to stratify high-risk pancreatic cancer patients with high efficacy and screened potential responding drugs for targeting strategy.